Anxiety and Alzheimer’s disease pathogenesis: focus on 5-HT and CRF systems in 3xTg-AD and TgF344-AD animal models - Reyna, Nicole C.; Clark, Benjamin J.; Hamilton, Derek A.; Pentkowski, Nathan S. (Frontiers in Aging Neuroscience, 2023)
Dementia remains one of the leading causes of morbidity and mortality in older adults. Alzheimer’s disease (AD) is the most common type of dementia, affecting over 55 million people worldwide. AD is characterized by distinct neurobiological changes, including amyloid-beta protein deposits and tau neurofibrillary tangles, which cause cognitive decline and subsequent behavioral changes, such as distress, insomnia, depression, and anxiety. Recent literature suggests a strong connection between stress systems and AD progression. This presents a promising direction for future AD research. In this review, two systems involved in regulating stress and AD pathogenesis will be highlighted: serotonin (5-HT) and corticotropin releasing factor (CRF). Throughout the review, we summarize critical findings in the field while discussing common limitations with two animal models (3xTg-AD and TgF344-AD), novel pharmacotherapies, and potential early-intervention treatment options. We conclude by highlighting promising future pharmacotherapies and translational animal models of AD and anxiety.